Disparities in Eye Care Utilization During the COVID-19 Pandemic - Elam, Angela R. (Am J Ophthalmol, 2022)
PURPOSE: To assess the relationship between telemedicine utilization and sociodemographic factors among patients seeking eye care. DESIGN: Comparative utilization analysis. METHODS: We reviewed the eye care utilization patterns of a stratified random sample of 1720 patients who were seen at the University of Michigan Kellogg Eye Center during the height of the COVID-19 pandemic (April 30 to May 25, 2020) and their odds of having a video, phone, or in-person visit compared with having a deferred visit. Associations between independent variables and visit type were determined using a multinomial logistic regression model. RESULTS: Older patients had lower odds of having a video visit (P = .007) and higher odds of having an in-person visit (P = .023) compared with being deferred, and in the nonretina clinic sample, older patients still had lower odds of a video visit (P = .02). Non-White patients had lower odds of having an in-person visit (P < .02) in the overall sample compared with being deferred, with a similar trend seen in the retina clinic. The mean neighborhood median household income was $76,200 (±$33,500) and varied significantly (P < .0001) by race with Blacks having the lowest estimated mean income. CONCLUSION: Disparities exist in how patients accessed eye care during the COVID-19 pandemic with older patients—those for whom COVID-19 posed a higher risk of mortality—being more likely to be seen for in-person care. In our affluent participant sample, there was a trend toward non-White patients being less likely to access care. Reimbursing telemedicine solely through broadband internet connection may further exacerbate disparities in eye care.